Genotypic Characterization of Rhizopus Spp. Tempeh and Usar: Traditional Inoculum of Tempeh in Indonesia - Anastasia Tatik Hartanti; Adi Yulandi; tati barus; Jason Wiranata Sanjaya; Vivitri Dewi Prasasty; David Tandjung (Microbiology Indonesia, 2020)
Abstract. Soybeans tempeh (tempeh) is processed by fermentation using Rhizopus spp. Tempeh is an important source of protein in Indonesia. The traditional inoculum in fermentation locally is known as Usar which is made from the leaves of Hibiscus tiliaceus. However, Rhizopus information from Usar is still limited. Therefore, this study aims to identify and investigate the genetic diversity of Rhizopus species from Usar and tempeh based on the Internal Transcribed Spacer (ITS) sequence and the Random Amplified Polymorphic DNA (RAPD) markers. Twenty-three Rhizopus strains were isolated from Usar and ten Rhizopus strains were isolated from tempeh. Based on ITS sequences, the isolates were similar to R Rhizopus microsporus (30 isolates) and Rhizopus delemar (3 isolates) with 98-99% similarity. The genetics of R. microsporus and R. delemar are varied and different from the genetics of R. microsporus from tempeh. The growth temperature of R. microsporus varies from 33 to 48Â°C and R. delemar can grow to a maximum at 33Â°C. The role of R. microsporus and R. delemar from Usar in determining the quality of tempeh is still limited. Therefore, it needs to be investigated further.